Remote Impact of Typhoon In‐Fa on the Catastrophic Flood Over Henan, Inland of China in July 2021 - Zhiqi Yan; Wanyi Sun; Congwen Zhu; Boqi Liu; Yuejian Zhu; Ning Jiang; Yuhan Yan (Geophysical Research Letters)
Abstract It has been shown the catastrophic flood in Henan, inland of China in July 2021, was strongly influenced by Typhoon In‐Fa in the western North Pacific. However, the remote impact of Typhoon In‐Fa via the monsoonal flow has not yet been clearly addressed. Our results show the In‐Fa amplified the East Asian Summer Monsoon (EASM) flow through potential vorticity advection, strengthening a mid‐latitude anticyclone in the troposphere over Northeast Asia, steering northward track of In‐Fa via enhanced cyclonic vorticity in its north. The cross‐time scale interaction between In‐Fa and the EASM intensified easterly winds, facilitated long‐distance moisture transport, and resulted in this catastrophic flooding. These findings reveal the remote impact of typhoon via the dynamical interaction with EASM flow, which better explains the extremity of this flooding.